The Effect Of Harvest Age On Seed Quality In Three Different Varieties Of Cayenne Pepper - Ilham Jati Nugroho; Syaiful Anwar; Florentina Kusmiyati (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
The aim of this study was to examine the effect of harvesting age which gives the best quality of cayenne pepper seeds, the influence of plant varieties on the quality of cayenne pepper seeds, and the interaction of harvesting age with plant varieties on the quality of chili pepper seeds. Field research was carried out from August to December 2021 at the Screenhouse of the Faculty of Animal Husbandry and Agriculture, Diponegoro University. The study used a 3x4 Split Plot experimental design on the basis of a Randomized Block Design with 3 replications. The main plots were: cayenne pepper varieties V1 = Sigantung, V2 = Wijaya, V3 = Bara. Sub-plots, namely: harvesting age consisted of P1 = 37 Day After Anthesis (DAA), P2 = 41 DAA, P3 = 45 DAA, and P4 = 49 DAA. The data obtained were then analyzed using analysis of variance and further tested with Duncan's Multiple Range Test (DMRT) at the 5% level. The results showed that harvesting ages of 37 and 41 HSA increased plant height, fruit length and fruit weight while harvesting ages of 49 HSA increased time to flower appearance, seed yield, seed vigor and seed viability. Cayenne with the Sigantung variety was able to increase plant height, fruit diameter, fruit weight, seed moisture content, seed wet weight, and seed vigor. There is an interaction between cayenne pepper variety and harvesting age on plant height and flower appearance parameters.